ANALYSIS OF NARRATIVE STRUCTURE AND FUNCTION IN THE VIDEO "UNDERSTANDING DANANTARA EASILY": TODOROV AND PROPP'S STUDY OF THE WORK OF THE MALAKA PROJECT - Irfan Azis Fahrudin; Catur Nugroho (International Journal of Cultural and Social Science, 2026)
The development of digital media presents challenges in delivering complex economic information to the wider community. This understanding gap encourages the emergence of communication strategies that use simple language and everyday narratives. This study aims to examine how narrative strategies are used in simplifying economic issues on YouTube content, considering that previous narrative studies focused more on films and fictional works. This study uses a descriptive qualitative design with a narrative analysis approach to the video Understanding Danantara with Ease by Malaka Project. The analysis was carried out using the framework of Tzvetan Todorov's narrative structure and the character function of Vladimir Propp. The results of the study show that the narrative is arranged through a classic fairy tale plot with an open ending that serves as a simulation of economic policy risks. In addition, the use of family metaphors and dual character construction allows for the simplification of issues without removing critical content. This study concludes that social media narratives can function as a bridge of public economic literacy that encourages understanding as well as audiences' reflective attitudes towards policy risks.